2020
DOI: 10.1099/mic.0.000956
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa is capable of natural transformation in biofilms

Abstract: Natural transformation is a mechanism that enables competent bacteria to acquire naked, exogenous DNA from the environment. It is a key process that facilitates the dissemination of antibiotic resistance and virulence determinants throughout bacterial populations. Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen that produces large quantities of extracellular DNA (eDNA) that is required for biofilm formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
0
30
1
Order By: Relevance
“…The absence of surface motility of the pilU mutant observed here for A. baumannii phenocopies that of P. aeruginosa ( 65 ). Despite this commonality between the two organisms, a recent study by Nolan et al demonstrated that TFP were dispensable for low levels of natural transformation of P. aeruginosa ( 29 ), which contrasted with our findings. Here, we demonstrated that apart from PilU, the pilus components were essential for A. baumannii ’s natural transformability ( Fig.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The absence of surface motility of the pilU mutant observed here for A. baumannii phenocopies that of P. aeruginosa ( 65 ). Despite this commonality between the two organisms, a recent study by Nolan et al demonstrated that TFP were dispensable for low levels of natural transformation of P. aeruginosa ( 29 ), which contrasted with our findings. Here, we demonstrated that apart from PilU, the pilus components were essential for A. baumannii ’s natural transformability ( Fig.…”
Section: Resultscontrasting
confidence: 99%
“…There are different types of TFP regulatory systems which exist in both competent and noncompetent bacteria. A major TFP regulatory system that has been studied in Pseudomonas aeruginosa (a bacterium that was only recently reclassified as naturally transformable [ 29 ]) is the two-component system (TCS) PilSR ( 30 32 ). The current model of this TCS suggests that extended pili are sensed due to the lack of inner membrane-associated PilA subunits that would otherwise interact with the atypical sensor histidine kinase PilS.…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary process of natural selection, gene loss and acquisition [ 217 , 218 ], natural genetic transformation [ 219 ], horizontal gene transfer [ 220 ], and emergence of hypermutators during acute VAP and/or chronic CF lung infection can lead to changes in antimicrobial resistance (AMR) and virulence behavior of P. aeruginosa [ 210 , 221 ]. The P. aeruginosa pan-genome contains a collection of 3,010 putative and plasmids DNA genes obtained by horizontal gene transfer with 5% to 12% encoding AMR and virulence genes [ 222 ].…”
Section: Genetic Transfer Drug Resistance and Increased Virulencementioning
confidence: 99%
“…Finally, the biofilm is an ideal environment for HGT events [8], which contribute to the spread of resistance determinants. Conjugation events are favored by close contact between cells of different strains and/or species [36]; moreover, it has recently been suggested that P. aeruginosa biofilms can achieve a natural competence to acquire both genomic and plasmid DNA [37]. This is a cause of particular concern for chronic CF patients, whose lungs are often colonized by different antibiotic-resistant strains, a condition that has the potential to give rise to multidrug resistance [38].…”
Section: P Aeruginosa Biofilms and Lung Infection In Cystic Fibrosis 21 P Aeruginosa Biofilms And Antibiotic Resistancementioning
confidence: 99%